ANALISIS KELAYAKAN PENERIMA BANTUAN COVID-19 MENGGUNAKAN METODE K–MEANS PADA KECAMATAN SAGULUNG KOTA BATAM - saputra, sahril; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2021)
During the pandemic, economic difficulties are part of the problems that occur to the residents of Tembesi Village, Sagulung District. Cash Social Assistance, Non-Cash Food Assistance, and Family Hope Program are several types of assistance that have been received by residents of Tembesi Village, but in its distribution, there are still many beneficiaries who do not meet the criteria based on the rules given by the government. K-Means Clustering Analysis method was chosen to solve this problem. This study aims to find beneficiaries who really deserve assistance of Cash.Social.Assistance, Non-Cash.Food.Assistance, and Family.Hope Program with the following criteria: poor people, not working, and not receiving more than one aid. This study uses 92 recipient data as research samples to be processed and the results obtained from this research are the criteria for not working with a value of C1 0.250 and C2 0.969 which have the highest feasibility level compared to the other two criteria.